Pemanfaatan Kompos Kulit Buah Kakao Pada Pertumbuhan Bibit Kakao Hibrida (Theobroma cacao L) (Jurnal Agro Teknologi Tropika, 2013)
Cacao (Theobroma cacao L) is one of the potential export commodity as foreign exchange income. Beside thedemand for cacao keep increasing cause of cacao processing industrial growth. The cocoa cultivation start frompreparing the seeds from a fine variety and applying right cultivation methode. This research aimed to determine theeffect of cacao pods compost on the growth of cocoa hybrid seedlings and was held on Engineering Laboratory, Facultyof Agriculture, University of Riau for 6 months, starting from May to October 2012. The design used was CompletelyRandomized Design (CRD), which consists of 5 treatments that are 0, 25, 50, 75 and 100 gram per polybag of cacao podscompost and 3 replications for each treatment. The provision of treatment which show that by giving cacao podscompost with dose of 100 g per polybag gave best seedling growth than another treatments.Keywords : hybrid cacao , compost, cacao pods